Exploring Students' Experiences in Using YouTube Videos as a Medium for English Listening Practice - Aulia Amalia Alimuddin, Nur (Journal of Indonesian Progressive Education, 2026)
This study explores students’ experiences in using YouTube videos as a medium for English listening practice. The research was conducted to understand how students utilize YouTube to improve their listening skills, the factors that influence its effectiveness, and the challenges they encounter during the learning process. Using a qualitative case study approach, data were collected through semi-structured interviews and non-participant observations involving eight non-English major students from STAI Al-Furqan Makassar. The findings reveal that YouTube provides students with authentic listening materials, flexible learning opportunities, and increased motivation due to its engaging and varied content. Students reported using strategies such as note-taking, repetition, and the use of English subtitles to enhance comprehension. However, challenges such as understanding diverse accents, maintaining focus, and ensuring consistent access to stable internet connections were also identified. Despite these limitations, YouTube proves to be an effective medium for developing students’ listening comprehension and fostering autonomous learning in a digital learning environment. The study recommends that educators provide structured guidance to maximize the pedagogical potential of YouTube as an interactive and learner-centered tool in English language learning.